INFORMATION ABOUT THE VILLAGES OF THE INHABITANTS OF THE GUZOR STATION OF THE EMIRATE OF BUKHARA BY AMLOK (late 19th – early 20th centuries) - Ergashev U. Q. (Web of Journals Publishing, 2024)
At the end of the XIX century - the beginning of the XX century, the residential addresses of the inhabitants of the Guzor Principality of the Bukhara Emirate were analyzed according to the properties, and comments were made about the villages and clans of the residents. Some promising data on these issues are discussed in the article.
Keywords: Principality, “ amlok” , kovcnin, kungirot, saroy, batosh, harduri, ulus,kaychili.